We can have peace in the Holy Land a plan that will work - Carter, Jimmy 1924- (Simon & Schuster, 2009)
Nobel Peace Laureate Jimmy Carter argues that the present moment is a unique time for achieving peace in the Middle East--and he offers a bold and comprehensive plan. For the last three decades, as President of the United States and as founder of The Carter Center, Carter has studied the complex and interrelated issues of the region's conflicts and has been actively involved in reconciling them. He knows the leaders of all factions who will need to play key roles, and he sees encouraging signs. Carter describes the history of previous peace efforts and why they fell short. He argues persuasively that the road to a peace agreement is now open and that it has broad international and regional support. Most of all, since there will be no progress without courageous and sustained U.S. leadership, he says the time for progress is now, and President Barack Obama is committed to a personal effort to exert that leadership.